Pilot study of a novel lumen‐apposing metal stent for endoscopic ultrasound‐guided procedures in porcine models - Benedetto Mangiavillano; Gianluca Franchellucci; Francesco Auriemma; Daryl Ramai; Alberto Larghi; Danilo Paduano; Diletta De Deo; Federica Calabrese; Carmine Gentile; Matteo Fiacca; Antonio Facciorusso; Alessandro Repici (DEN Open)
Abstract Lumen‐apposing metal stents have expanded the therapeutic potential of interventional endoscopic ultrasound (EUS). The Hot‐Spaxus (Taewoong Medical Co., Ltd.), the second most commonly utilized lumen‐apposing metal stent, requires two operators for its release which has been considered a limitation compared to other lumen‐apposing metal stents. We aimed to test the feasibility and the technical success of a newly available version of the Hot‐Spaxus stent equipped with an innovative handle delivery system for EUS‐guided interventional procedures. We conducted a pilot study using porcine models. The novel Hot‐Spaxus 2 was tested by performing four EUS‐guided procedures including four EUS‐guided gallbladder drainage and 12 EUS‐guided gastrojejunostomy) procedures. Technical success was reported in 100% of cases. The mean procedure time for EUS‐guided gatrojejunostomyJ and EUS‐guided gallbladder drainage was 23.85 min (standard deviation 3.41) and 16.15 min (standard deviation 2.72), respectively. The distal and proximal flanges were safely released by the endosonographer without any complications. No adverse events were reported. In conclusion, the novel Hot‐Spaxus 2 stent may represent an improvement compared to the prior Spaxus model. Unlike its predecessor, this newly designed stent eliminates the need for two endoscopists and can be deployed by a single operator. Further human studies are necessary to validate its clinical effectiveness.